2015
DOI: 10.7577/formakademisk.1313
|View full text |Cite
|
Sign up to set email alerts
|

From Gender-segregated Subjects to Multi-material Craft: Craft Student Teachers’Views on the Future of the Craft Subject

Abstract: This paper describes the views of student teachers of craft about the future of craft as a school subject. The study was conducted at the University of Turku, Department of Teacher Education, in Rauma in 2014. The literature review revealed that the subject of craft in Finnish basic education is understood as a dialog between the maker and the materials. However, teaching and learning craft in schools and in teacher education has a strong gender-based tradition. The aim of this study is to investigate student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 24 publications
0
17
0
12
Order By: Relevance
“…The tools, machines, equipment, devices and craft techniques that constitute the technology of craft are no more than instruments. In the experiential and explorative acquisition of information in a multi‐material ‘hands‐on’ making process (Lepistö & Lindfors ) and learning‐in‐doing (Pöllänen & Urdziņa‐Deruma ), the individual gains a concrete understanding of the material world (Groth & Mäkelä ; Väänänen et al ) and abilities to relate to the world in a new, more sustainability and well‐being enhancing way (Pöllänen ; Veber & Syrjäläinen ; Väänänen et al ). This kind of embodied knowledge requires designing, thinking, reflecting, exploring and problem‐solving during all phases of the craft process (Kangas ).…”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tools, machines, equipment, devices and craft techniques that constitute the technology of craft are no more than instruments. In the experiential and explorative acquisition of information in a multi‐material ‘hands‐on’ making process (Lepistö & Lindfors ) and learning‐in‐doing (Pöllänen & Urdziņa‐Deruma ), the individual gains a concrete understanding of the material world (Groth & Mäkelä ; Väänänen et al ) and abilities to relate to the world in a new, more sustainability and well‐being enhancing way (Pöllänen ; Veber & Syrjäläinen ; Väänänen et al ). This kind of embodied knowledge requires designing, thinking, reflecting, exploring and problem‐solving during all phases of the craft process (Kangas ).…”
Section: Research Resultsmentioning
confidence: 99%
“…In a multi‐material learning environment, students can design and produce solutions to design challenges and reflect on the holistic craft‐based process and solutions (Jaatinen et al ). As Lepistö & Lindfors () noted, students need not, however, engage with all of the available materials and techniques but should be aware of a range of material and technological means to be used. Härkki et al () found that if the materials are known in advance of the design process, the materials may guide the solutions or students will not know what to do with the new materials.…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historisk er kunst og håndverksfaget innskrevet i en nordisk tradisjon, med tradisjonell kjønnsmessig materialdifferensiering. Dette kommer jevnlig opp til diskusjon i forbindelse med laereplanrevisjoner i skole og laererutdanning i de ulike landene (Kjosavik, 2003;Lepistö & Lindfors, 2015;Sigurdson, 2014;Skoleverket, 2015;Westerlund, 2015). Formingsideen som kom inn i norsk skole i 1960 representerte et klart brudd med denne tradisjonen, og en beveget seg mot materialuavhengig arbeid med estetiske prosesser (Forsøksrådet for skoleverket, 1960, heretter kalt F60).…”
Section: Ingvard Bråten Og Jorunn Spord Borgenunclassified